2015
DOI: 10.1002/aelm.201500301
|View full text |Cite
|
Sign up to set email alerts
|

Fully Drawn All‐Organic Flexible Transistors Prepared by Capillary Pen Printing on Flexible Planar and Curvilinear Substrates

Abstract: Printing technologies are instrumental to the fabrication of low‐cost lightweight flexible electronic devices and circuits, which are necessary to produce wearable electronic applications. However, attaining fully printed devices on flexible films over large areas has typically been a challenge. Here, the fabrication of fully drawn all‐organic field‐effect transistor (FET) arrays on mechanically flexible substrates using a capillary‐pen printing method is demonstrated. A highly crystalline organic semiconducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
(85 reference statements)
0
25
0
Order By: Relevance
“…Traditional inorganic substrates are rigid and brittle, so they are not directly applicable to flexible devices. Polymer materials such as polyethylene terephthalate (PET), [19][20][21] polyethylene-2, 6-naphthalate (PEN), [22][23][24] and polydimethyl siloxane (PDMS) [25][26][27] are used widely due to their chemical stability, ideal mechanical and physical properties. The mechanical flexibility test in earlier studies mainly included repeated inward or outward bending with strains S induced on the surface of substrate (Figure 2a,b).…”
Section: Flexible Substratementioning
confidence: 99%
“…Traditional inorganic substrates are rigid and brittle, so they are not directly applicable to flexible devices. Polymer materials such as polyethylene terephthalate (PET), [19][20][21] polyethylene-2, 6-naphthalate (PEN), [22][23][24] and polydimethyl siloxane (PDMS) [25][26][27] are used widely due to their chemical stability, ideal mechanical and physical properties. The mechanical flexibility test in earlier studies mainly included repeated inward or outward bending with strains S induced on the surface of substrate (Figure 2a,b).…”
Section: Flexible Substratementioning
confidence: 99%
“…The inks limit the screen‐printing technique because their formulation uses organic solvents that are susceptible to temperature and humidity, which vary the standardized concentrations and viscosity. Furthermore, the technique presents low resolution, high ink waste, and imprecision due to the low contact pressure during fabrication ,…”
Section: Fabrication Of Paper‐based Electrochemical Devicesmentioning
confidence: 99%
“…The average field‐effect mobility, threshold voltage, and on/off current ratio were 0.025 cm 2 V −1 s −1 , 3 V, and 10 5 , respectively. Moreover, it was demonstrated that an array of all‐organic flexible FETs could be drawn on flexible substrates using only the capillary‐pen printing method ( Figure ) . OFETs with a bottom‐gate/bottom‐contact configuration were fabricated as follows (Figure b).…”
Section: Heterogeneous Patterning Of Organic Materialsmentioning
confidence: 99%
“…Photographs showing each stage of a sequential capillary‐pen printing process for fabrication of a TIPS‐PEN OFET array (bottom). Reproduced with permission . Copyright 2015, John Wiley & Sons.…”
Section: Heterogeneous Patterning Of Organic Materialsmentioning
confidence: 99%